Chronic diseases attributable to a diet rich in processed meat in Brazil: Burden and financial impact on the healthcare system - Rocha, Carla Eduarda Faustino; Parajára, Magda do Carmo; Machado, Ísis Eloah; Vegi, Aline Siqueira Fogal; Menezes, Mariana Carvalho de; Meireles, Adriana Lúcia (Frontiers in Nutrition, 2023)
Objectives: This study aimed to describe the burden of chronic noncommunicable diseases (NCDs) attributed to a diet rich in processed meat (PM) between 1990 and 2019 in Brazil and Federative Units, and the financial burden on the Unified Health System (SUS) in 2019. Methods: Secondary data from the Global Burden of Disease (GBD) and SUS Information Systems were used in this study. The metrics used to assess the burden of NCDs attributable to PM consumption were deaths and disability-adjusted life years (DALYs). The age-standardized rates per 100,000 people for both sexes are presented. The cost of hospitalizations and outpatient procedures covered by SUS for the treatment of NCDs attributable to PM consumption was estimated using the population-attributable fraction. The amount spent was converted into international dollars. Results: The age-standardized mortality rates decreased between 2009 and 2019. The cost of hospitalization and outpatient procedures in Brazil for NCDs attributable to the consumption of PM was US$8,672,668.30, of which US$5,887,880.13 was spent on ischemic heart disease, US$2,626,585.15 on colorectal cancer, and US$158,203.02 on type II diabetes mellitus. Conclusion: The NCD burden showed a slight decrease during the years evaluated, while the financial burden was high in 2019, with higher treatment costs for ischemic heart disease. These results can guide political, economic, and health education interventions to advance the fight against NCDs.